Effect of Precursor on Speciation and Nanostructure of SiBCN Polymer‐Derived Ceramics. Issue 5 (29th January 2013) - Widgeon, Scarlett; Mera, Gabriela; Gao, Yan; Sen, Sabyasachi; Navrotsky, Alexandra; Riedel, Ralf; Colombo, P.
<x xml:space="preserve">Abstract</x> A comparative structural study of silicon borocarbonitride polymer‐derived ceramics synthesized using polyborosilylcarbodiimide and polyborosilazane precursors is carried out using high‐resolution, multinuclear, one‐ and two‐ dimensional NMR spectroscopy. The polyborosilylcarbodiimide‐derived ceramics contain relatively pure Si3N4 and C nanodomains with the BN domains being present predominantly at the interface such that the bonding at the interface consists of Si–N–B, Si–N–C, and B–N–C linkages. In contrast, the structure of the polyborosilazane‐derived ceramics consists of significant amount of mixed bonding in the nearest‐neighbor coordination environments of Si and B atoms leading to the formation of SiCxN4−x (0 ≤ x ≤ 4) tetrahedral units and BCN2 triangular units. The interfacial region between the SiCN and C nanodomains is occupied by the BCN phase. These results demonstrate that the chemistry of the polymeric precursors exerts major influence on the microstructure and bonding in their derived ceramics even when the final chemical compositions of the latter are similar.